Virulence, resistance, and genetic diversity of Vibrio parahaemolyticus recovered from commonly consumed aquatic products in Shanghai, China. (November 2020) - Su, Chenli; Chen, Lanming
Abstract: Vibrio parahaemolyticus can cause severe gastroenteritis, septicaemia and even death in humans. Continuous monitoring of V. parahaemolyticus contamination in aquatic products is imperative for ensuring food safety. In this study, we isolated and characterized 561 V. parahaemolyticus strains recovered from 23 species of commonly consumed shellfish, crustaceans, and fish collected in July and August of 2017 in Shanghai, China. The bacterium was not isolated from two fish species Carassius auratus and Parabramis pekinensis . The results revealed a very low occurrence of pathogenic V. parahaemolyticus carrying the toxin genes trh (0.2%) and tdh (0.0%). However, high percentages of resistance to the antimicrobial agents ampicillin (93.0%), rifampin (82.9%), streptomycin (75.4%) and kanamycin (50.1%) were found. A high incidence of tolerance to the heavy metals Hg 2+ (74.7%) and Zn 2+ (56.2%) was also observed in the isolates. ERIC-PCR-based fingerprinting of MDR isolates (77.5%) revealed 428 ERIC-genotypes, demonstrating remarkable genetic variation among the isolates. The results of this study support the urgent need for food safety risk assessment of aquatic products. Highlights: A very low occurrence of pathogenic V. parahaemolyticus ( trh, 0.2%) in 561 isolates High percentages of resistance to antimicrobial agents AMP, RIF, STR, and KAN High incidence of tolerance to heavy metals Hg 2+, and Zn 2+ Different resistance profiles among 23 species and 3 kinds of aquatic products Divergent ERIC-genotypes of the V. parahaemolyticus isolates